2011
DOI: 10.2355/isijinternational.51.1296
|View full text |Cite
|
Sign up to set email alerts
|

High Carbon Ferro-chromium Production by Self-reducing Process: Effects of Fe–Si and Fluxing Agent Additions

Abstract: The technology of self-reducing pellets for ferro-alloys production is becoming an emerging process due to the lower electric energy consumption and the improvement of metal recovery in comparison with the traditional process. This paper presents the effects of reduction temperature, addition of ferro-silicon and addition of slag forming agents for the production of high carbon ferro-chromium by utilization of selfreducing pellets. These pellets were composed of Brazilian chromium ore (chromite) concentrate, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
0
12
0
2
Order By: Relevance
“…The mechanism of reduction they proposed consisted in two stages: the first stage was the reaction between CO and chromite, while the second stage was carried out after the slag formation, where the reduction process slowed down. Other similar research was realised by Zambrano et al, 11 who studied the effect of iron-silicon addition on reaction efficiency to obtain alloys with high carbon content iron-chromium under argon atmosphere. The process was studied at temperatures ranging from 1500 to 1600°C, and the authors found that the reaction rate increased with the temperature as long as the slag had not yet been formed; in the presence of slag, the reaction time increased.…”
Section: Introductionmentioning
confidence: 88%
“…The mechanism of reduction they proposed consisted in two stages: the first stage was the reaction between CO and chromite, while the second stage was carried out after the slag formation, where the reduction process slowed down. Other similar research was realised by Zambrano et al, 11 who studied the effect of iron-silicon addition on reaction efficiency to obtain alloys with high carbon content iron-chromium under argon atmosphere. The process was studied at temperatures ranging from 1500 to 1600°C, and the authors found that the reaction rate increased with the temperature as long as the slag had not yet been formed; in the presence of slag, the reaction time increased.…”
Section: Introductionmentioning
confidence: 88%
“…Ferric chloride helps coarsen the iron particles and can effectively help in separating metal from the reduced product 5, 6. Zambrano et al,7 observed that the addition of 2% Fe–Si in the chromite pellet accelerates the reaction rate by around six times.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Fe-Si was used as an additive in the carbothermic reduction of chromite. 13,14) It was observed that the addition of Fe-Si enhanced the carbothermic reduction of chromite. In present study, an attempt was made to enhance the carbothermic reduction of PTC by the addition of Fe-Si.…”
Section: Introductionmentioning
confidence: 99%